Analyzing governance challenges using Process Net-Map: a case study of a government microcredit scheme in Bangladesh. (18th August 2021) - Parvin, Mst Tania; Birner, Regina
Abstract : Purpose: This paper aims to examine the governance challenges confronted by a government microcredit program in Bangladesh following a case study approach. Design/methodology/approach: A novel qualitative research tool called process net-map (PNM) was applied to develop a framework for visual understanding of the exact credit implementation process and to identify the actors responsible for creating governance challenges. Key informant interviews were also conducted to identify and distinguish the challenges faced by both the supply-side and demand-side stakeholders. Findings: The findings reveal that the studied case faced problems in allocating adequate resources to human and physical capacity development. It was combined with the shortage of funds that made it impossible to meet the clients' expectations. The lack of legal and regulatory framework disabled the organization from controlling political influence and corruption in the system. Moreover, the policy of lending only to groups proved counterproductive as it led to the exclusion of potentially viable borrowers. Practical implications: The key recommendation of the study is on increasing the microcredit fund and a reform of the group lending policy along with several other recommendations. Originality/value: The PNM is a newly developed participatory mapping technique that has not been applied in the field of microfinance. Therefore, the use of this method may add new knowledge of conducting an in-depth analysis of why such challenges are associated with mostly public microfinance programs and how they are linked to the implementation process. The challenges encountered are relevant for the implementation of developmental programs that are dependent on the allocation of public funds.